The embodiment of power and communalism in space and bodily contact - Schubert, T.; Waldzus, S.; Seibt, C. (Embodied grounding: Social, cognitive, affective, and neuroscientific approaches, 2008)
Imagine you visit a village on some remote island, with a culture with which you are not familiar. On this island, you discover a number of strange behaviors of which you try to make sense. For instance, some of the islanders rub their noses with each other as a greeting. You also learn that others eat potions “using combinations of ingredients such as rocks from the tallest mountain-peaks and epiphytes growing atop the highest trees” (Fiske, 2004, p. 95). How would you interpret these behaviors? Perhaps you would guess those with nose-to-nose contact are generally close to each other, and those eating the potions made of high things enjoy or attain high status. What you have figured out then are perhaps the two most basic and important dimensions of social relations: community relations and power relations (Mead, 1934). What is the basis of such a judgment that relates unknown behaviors to social relations? In this chapter, we will approach this question from the standpoint of Relational Models Theory (RMT) developed by Fiske (1992; Fiske & Haslam, 2005). This theory identifies community and power as two of the basic relational models humans use to structure and coordinate their social interactions. In a nutshell, when people have a community relation or communal sharing (CS), they focus on what they have in common. Thus, resources are seen as common in a CS relation and shared according to needs.